Sosialisasi Pemanfaatan Quick Responden Code Indonesia Standard (Qris) dan Uang Eletronik (e-money) Untuk Pembelian E-book di Era RI 4.0 - Erdisna Erdisna; Deval Gusrion; Febriyanno Suryana (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
Technological developments offer many conveniences to the public, so many choices are offered, one of which is the use of electronic money. Electronic money is an alternative form of non-cash payment instrument that is currently widely used by the public, especially in Indonesia, the use of electronic money provides convenience in transactions. To facilitate digital money transactions, the government created an integrated payment gateway called Qris. Qris is a means of payment officially issued by Bank Indonesia for use in daily activities by the public, but the public has not fully used Qris as part of their payment transaction activities. There are many factors that cause these problems to occur including financial literacy, income and the basic concepts of the Technology Acceptance Model (TAM), namely the perceived ease of applying interest in using electronic money (e-money) and Qris.